2018
DOI: 10.1111/bph.14499
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional electron microscopy techniques for unravelling mitochondrial dysfunction in heart failure and identification of new pharmacological targets

Abstract: A hallmark of heart failure is mitochondrial dysfunction leading to a bioenergetics imbalance in the myocardium. Consequently, there is much interest in targeting mitochondrial abnormalities to attenuate the pathogenesis of heart failure. This review discusses (i) how electron microscopy (EM) techniques have been fundamental for the current understanding of mitochondrial structure–function, (ii) the paradigm shift in resolutions now achievable by 3‐D EM techniques due to the introduction of direct detection de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 158 publications
(177 reference statements)
0
19
0
Order By: Relevance
“…; Duvert, Mazat, & Barets, ), where the cristae of adjacent mitochondria align in a parallel fashion. This form of ‘kissing communication’ between mitochondria has been linked to cardiac function in rats (Cao & Zheng, ) and exercise in mice (Picard et al ., 2013 a ; see also Daghistani, Rajab, & Kitmitto, ). Thus, the density of IMM and proportion of IMJs may be crucial morphological components of mitochondrial performance.…”
Section: Mitochondrial Behaviour Morphology and Performancementioning
confidence: 97%
“…; Duvert, Mazat, & Barets, ), where the cristae of adjacent mitochondria align in a parallel fashion. This form of ‘kissing communication’ between mitochondria has been linked to cardiac function in rats (Cao & Zheng, ) and exercise in mice (Picard et al ., 2013 a ; see also Daghistani, Rajab, & Kitmitto, ). Thus, the density of IMM and proportion of IMJs may be crucial morphological components of mitochondrial performance.…”
Section: Mitochondrial Behaviour Morphology and Performancementioning
confidence: 97%
“…The heart is not the exception since most of the cardiopathies are associated with alteration in mitochondrial morphology. Fragmented, swollen, reduced mitochondrial number, reduced cristae densities are the main morphological features of human heart failure which are nicely tabulated in Daghistani et al (2018) . Interestingly, different cardiac pathologies have shown distinct morphological mitochondria and cristae patterns.…”
Section: Mitochondria In Cardiac Cellsmentioning
confidence: 99%
“…Much of the cardiac literature describes a relationship between different cardiopathies and mitochondrial dysfunction. Daghistani et al (2018) , Chaanine (2019) showed that mitochondria changed their morphology from elongated to fragmented in heart failures. Lin and Kerkelä (2020) , that there is a reduction in ETC and bioenergetic capacity in cardiomyopathies; and Vasquez-Trincado et al (2016) , Bravo-San Pedro et al (2017) that mitochondrial dynamics and mitophagy are altered or reduced in cardiovascular diseases.…”
Section: Cardiac Mitochondria In Agingmentioning
confidence: 99%
“…Mitochondrial dysfunction is a hallmark of HF ( 8) and more recently identified as a feature of HFpEF (9) and DCM (10). While mitochondrial dysfunction is a broad term a recurring feature of HF both in the presence and absence of diabetes, is morphological remodelling of mitochondria, with reports of both swelling and fragmentation [for a review see (11)]. Mitochondrial size, shape and distribution (factors dictating function) are regulated by mechanisms grouped under the umbrella term "mitochondrial dynamics, " which also encompasses mitochondrial turnover, mitophagy and biogenesis, as reviewed by (12).…”
Section: Introductionmentioning
confidence: 99%